How repayments manipulate our perceptions about loan dynamics after a boom - Ramón Adalid; Matteo Falagiarda (European Central Bank (ECB), 2018)
We propose a method to decompose net lending flows into loan origination and repayments. We show that a boom in loan origination is transmitted to repayments with a very long lag, depressing the growth rate of the stock for many periods. In the euro area, repayments of the mortgage loans granted in the boom preceding the financial crisis have been dragging down net loan growth in recent years. This concealed an increasing dynamism in loan origination, especially during the last wave of ECB's non-standard measures. Using loan origination instead of net loans has important implications for understanding macroeconomic developments. For instance, the robust developments in loan origination in recent times explain the strengthening in housing markets better than net loans. Moreover, credit supply restrictions during the crisis are estimated to be smaller. Overall, there is a premium on using loan origination and repayments in economic models, especially after large booms.
Keywords: E17; E44; G01; D14; 330; new lending; loan repayments; amortisation rate; housing markets